Historiography of the Caspian flotilla - Magomedhabib R. Seferbekov (Кавказология, 2022)
Based on pre-revolutionary, Soviet and post-Soviet sources and literature, using comparative historical, typological, chronological, systemic and retrospective general scientific methods, the article provides a historiography of the Caspian Flotilla. The beginning of this process dates back to the time of the existence of the medieval Old Russian state and the Grand Duchy of Moscow, during the years of their existence, trade and economic relations of Russia along the Caspian Sea with the cities and states of the Eastern Caucasus were being established. A significant place in Russian historiography is given to establishing the Muscovite state in the Volga and Caspian basins and the founding of the Russian fortress city of Astrakhan in the Volga delta, which contributed to the development of shipbuilding and shipping on the Caspian Sea and served as a prologue to the founding of the Volga-Caspian military flotilla. Much attention in Russian and Soviet historiography is paid to the events of the early 18th century, when Russia, under the leadership of Peter the Great, achieved especially splendid victories on the coast of the Caspian Sea. As the authors note, the conquest by the Russian Empire was because of the Persian campaign of 1722–1723. The Western Caspian has changed the balance of power in the geopolitical confrontation between regional powers in favor of Peter’s Russia. According to several authors, the Caspian flotilla becomes important with the coming to power of Catherine II and subsequent Russian emperors. Of particular importance in the confrontation with Persia was the Treaty of Gulistan concluded with it in 1813 and the Turkmanchay Treaty of 1828. In subsequent years, Russia anchored the western coast of the Caspian Sea and the South Caucasus. At the end of the XIX-XX centuries the main base of the Caspian flotilla is in Baku, in connection with which the sailors of the flotilla were drawn into the events of 1905-1907, February-October 1917, the Civil War in the Caucasus, during which the Volga-Caspian flotilla was created. In the initial period of the Great Patriotic War, the Caspian Flotilla gained the status of a front formation. After the collapse of the USSR, the Caspian flotilla was divided between Russia and Azerbaijan, and the primary base was moved from Baku, first to Astrakhan, and then to Kaspiysk. Extensive pre-revolutionary, Soviet and Russian historiography of the history of the Caspian Flotilla testifies to the importance of the Caspian Sea and the Eastern Caucasus in the geopolitics of Russia from the Middle Ages to modern times.